Thucydides and the politics of truth = Tukidydes i polityka prawdy - Morley, Neville (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Populism, fake news, international rivalries and plague: contemporary events seem to many commentators to echo those described by the ancient Greek historian Thucydides. There is a long tradition of seeing Thucydides as an authority on the present and future as well as the past. This is understood in different ways: historians emphasise the importance of historical knowledge, social scientists see him as a pioneer in normative political theory.
Keywords: Thucydides; history; politics; classical reception; Tukidydes (historyk grecki; między 471 a 460 p.n.e. - między 404 a 393 p.n.e.); historia; polityka; recepcja starożytności